Honouring Dennis Haskell: a poet, and an amigo of Asiatic and Asian literature - Quayum, Mohammad Abdul (Department of English Language and Literature IRKHS, IIUM, 2019)
This issue of Asiatic(Vol. 13, No. 2) is dedicated tothe life and works of Dennis Haskell (1948-),a long-standing friend of the Journal, who has been on itsAdvisory Board since the Journal’s inception.He is also an ardent champion of Asian literaturewhohas been at the forefront of literary representations of Australian-Asian interactions and has shown an extensive understanding of Asian cultures both in his creative and critical works.Together with Edwin Thumboo and late Bruce Bennett, he has been a driving force behind the Biennial Symposium on Literature and Culture in the Asia-Pacific Region, which began in 1982 and has been takingplace since every two years in different countries of the region, two of which (2009, 2017) were, indeed, hosted by the same institution where Asiaticis also housed, International Islamic University Malaysia(IIUM).Moreover, he came to IIUM as a visiting professor in 2018.